2010
DOI: 10.1007/s12161-010-9142-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Duplex Real-Time PCR for the Detection of Salmonella spp. in Different Food Products

Abstract: A 5′ nuclease duplex real-time polymerase chain reaction (PCR) assay was developed and validated with various food products for the specific and fast detection of Salmonella spp. in food. The assay used previously published primers in combination with a newly developed probe targeting the invA gene. An internal amplification control, which is coamplified in a duplex PCR, was included in the assay. The analysis of 1,934 natural food samples with real-time PCR and the cultural method in parallel resulted in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 36 publications
2
39
0
3
Order By: Relevance
“…A few validation studies have been reported for food samples that were spiked with Salmonella (8,9,11,12,42), but no validation studies have been reported for environmental samples. The primer sets that have been used for the amplification of Salmonella DNA by different methods differed in their detection limits, lacked disclosure of the internal amplification control (IAC) DNA sequence used (8,9,(11)(12)(13)(14), or did not include a wide range of epidemiologically important isolates. In addition, the matrices and levels of contaminating competing organisms present in each environmental sample appeared to be unique, making the validation of methods for screening environmental samples a challenge.…”
mentioning
confidence: 99%
“…A few validation studies have been reported for food samples that were spiked with Salmonella (8,9,11,12,42), but no validation studies have been reported for environmental samples. The primer sets that have been used for the amplification of Salmonella DNA by different methods differed in their detection limits, lacked disclosure of the internal amplification control (IAC) DNA sequence used (8,9,(11)(12)(13)(14), or did not include a wide range of epidemiologically important isolates. In addition, the matrices and levels of contaminating competing organisms present in each environmental sample appeared to be unique, making the validation of methods for screening environmental samples a challenge.…”
mentioning
confidence: 99%
“…Before artificial contamination, the presence of Salmonella spp. in samples was excluded by testing with the cultural method according to SRPS EN ISO 6579:2008 (ISO, ) and real‐time PCR method (Anderson et al, ). Then, 25 g of each artificially contaminated samples were mixed with 225 ml buffered peptone water (BPW) (Oxoid, UK), homogenized and incubated in accordance with SRPS EN ISO 6579:2008 (ISO, ).…”
Section: Methodsmentioning
confidence: 99%
“…Several real‐time PCR protocols were developed with the aim of detecting Salmonella spp. in food (Anderson et al, ; Josefsen, Krause, Hansen, & Hoorfar, ; Krämer et al, ; Malorny et al, ; Rodriguez‐Lazaro, Hernandez, Esteve, Hoorfar, & Pla, ). Also, there are a number of available kits that apply real‐time PCR method for the detection of Salmonella (Assurance GDS for Salmonella— BioControl Systems, Foodproof Salmonella Detection Kit—BIOTECON Diagnostics, GeneDisc Salmonella —Pall Corp., iQ‐Check Salmonella II Kit—BioRad, MicroSEQ Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, relative sensitivity, specificity and accuracy (SE/SP/AC), positive and negative predictive values (PPV/NPV) and the index kappa of concordance (κ) were estimated from these data. Calculations of these parameters were performed as previously described [28,40,41].…”
Section: Evaluation Of the Specificity Accuracy And Precision Of Thementioning
confidence: 99%